Changes of lipocalin type prostaglandin D-synthase in the seminal plasma of subfertile man - Leone, M G; Abdel, H H; Gennaro, G; Amici, S; Conte, D; Romanelli, F; Latini, M; Isidori, A; Saso, L; Silvestrini, B (Research communications in molecular pathology and pharmacology, 2001)
It was proposed that lipocalin type prostaglandin D synthase (L-PGD-S), a bifunctional protein both synthesizing PGD2 and transporting retinoids and other lipophilic ligands, could be involved in the development and the maturation of sperm. In the present study, the seminal plasma (SP) of 59 adult males was analyzed by standard WHO methods and immunoblotting, using a monospecific polyclonal antibody directed against L-PGD-S. Briefly, aliquots of SP (2.5 microl), were fractionated by polyacrylamide electrophoresis in the presence of sodium dodecyl sulfate, the blots were stained and densitometrically analyzed. To obtain quantitative data, the aliquot of SP was selected within the linear part of the dose/band intensity curve and a proper quality control was analyzed in all blots to normalize the intensity of the bands of different experiments. A significant reduction (p<0.05) of the L-PGD-S levels was observed in severe oligozoospermic patients compared to normozoospermic subjects and a significant correlation between L-PGD-S levels and sperm concentration was found, as reported by other authors. Further studies are warranted to evaluate the possible diagnostic and pharmacological applications of these observations.